Adverse Childhood Experiences Among University Student and The Relationship With Depression - Bagas Rahmatullah; Adellia Nurul; Channia Hasgat; Ginta Sellia Putri; Inggrid Nathania Tambunan; Siti Hawa Annisa Mantika; Andi Tenri Faradiba (People and Behavior Analysis, 2023)
In a research conducted by Hillis et al. (2016), worldwide, 1 billion children aged 2-17 years experience ACE in various forms, such as sexual abuse, emotional abuse, and neglect. Traumatic childhood experiences can potentially negatively affect health and well-being in the long term (Sacks, Murphey, and Moore, 2014). This research aims to determine the correlation between exposure to adverse childhood experiences and a tendency to depression. This study uses a quantitative approach with a statistical correlation test. There were 499 participants in this study with the ACE-IQ measuring instrument to measure the type of exposure to violence and the PHQ-9 to measure the level of depression. The statistical analysis showed a significant relationship between ACE and a tendency to depression with r=.43; p < .001. Therefore, based on the statistical analysis results using Pearson Correlation, we concluded a positive correlation between Adverse Childhood Experiences and a tendency to depression. However, this study still does not comprehensively explain the level of ACE exposure and depression regarding gender and age differences.